African Philosophy
X, 312 p.
Keywords: This publication is a continuation of two earlier series of chroni cles, Philosophy of the Mid-Century (Firenze 1958/59) and Con temporary Philosophy (Firenze 1968), edited by Raymond Klibansky. Like the other series, these chronicles provide a survey of significant trends in contemporary philosophical discussion from 1970 to 1985. The need for such surveys has, I believe, increased rather than decreased over the last years. The philosophical scene appears, for various reasons, more complex than ever before. The continuing process of specialization in most branches, the emergence of new schools of thought, the convergence of interest (thought not neces sarily of opinion) of different traditions upon certain problems, the increasing attention being paid to the history of philosophy in discussions of contemporary problems, and the growing signifi cance for philosophical discourse of the social, political and cul tural situation in various regions of the world are the most impor tant contributory factors. Surveys of the present kind are a valu able source of knowledge of this complexity and may as such be an assistance in renewing the understanding of one's own philo sophical problems. The surveys, it is to be hoped, may also help to strengthen a world-wide Socratic element of modern philosophy, the dialogue or Kommunikationsgemeinschaft. So far, five volumes have been prepared for the new series.